"THE LITTLE MERMAID": AN ANALYSIS OF THE TEXTUALITY CRITERIA AND ARGUMENTATIVITY IN THE TITLE OF A REPORT ON DISNEY'S NEW FILM VERSION - Costa Consentino, Elisângela; Cristina Cordeiro, Isabel; Cristina Guerreiro de Oliveira, Lolyane (Revista de Letras, 2025)
This study is based on the assumption that the text is seen from the notion of interaction. In this interactional approach, subjects are considered active agents who play a role in the construction of society. When creating the title of a story, the selection of words and linguistic resources should promote a positive interaction with the reader. Thus, this work aims to analyze the title of a report that deals with the repercussion of the last version of the movie "The Little Mermaid", by Walt Disney Studios. For this analysis, we adopted a theoretical-methodological approach based on the theory of Textual Linguistics, with the purpose of investigating the linguistic resources used in the title of this journalistic text. The corpus of the analysis is composed of the title and subtitle of the article published on the website bebe.com.br, published by Editora Abril. The analysis reveals that, especially in the context of journalism, headlines follow an evolutionary trajectory similar to that observed in advertising, in which informative objectivity is replaced by language designed to attract and persuade the public. The titles seek to impress the reader, instigating their interest in the content of the report.